2018
DOI: 10.1007/s00056-018-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dentoskeletal changes following Class II treatment using a fixed functional appliance: the Austro Repositioner

Abstract: The Austro Repositioner was effective for short-term treatment of skeletal Class II malocclusion resulting from the retrusion of the mandible in both dolicho- and brachyfacial patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The results observed in the present study regarding the stability at one-year follow-up confirm the effects observed in the short term [ 10 ] and, therefore, indicate that the Austro Repositioner is an effective fixed functional device for treating skeletal Class II malocclusion with a mandibular origin. It also allows the vertical dimension to be modified, so it would be especially indicated for treatment of patients with a brachyfacial growth pattern.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The results observed in the present study regarding the stability at one-year follow-up confirm the effects observed in the short term [ 10 ] and, therefore, indicate that the Austro Repositioner is an effective fixed functional device for treating skeletal Class II malocclusion with a mandibular origin. It also allows the vertical dimension to be modified, so it would be especially indicated for treatment of patients with a brachyfacial growth pattern.…”
Section: Discussionsupporting
confidence: 85%
“…Subjects were treated in two phases. The first phase comprised the Austro Repositioner appliance, according to a previously described protocol [ 10 ] ( Figure 1 ), specially designed by brachyfacial patients; in brief, the acrylic resin wedge was extended to the upper incisors, and in this anterior segment, the wedge was 1.0–1.5 mm thicker.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations